Pannexin channels in inflammation and tumorigenesis - Jiang, Mengmeng; Li, Xiaojia; Xie, Keping (Frontiers in Cell and Developmental Biology, 2025)
Pannexin (Panx) channels are oligomeric heptamers of PANX proteins, comprising Panx1, Panx2 and Panx3. These channels facilitate the extracellular release of signaling molecules up to 1.5 kDa in size, including adenosine triphosphate (ATP), amino acids, ions, and other metabolites. These signaling molecules can activate receptors either on their cells of origin or neighboring cells, triggering downstream signaling cascades that mediate various physiological responses. Current pharmacological inhibitors of Panx channels include Food and Drug Administration (FDA)-approved drugs such as Carbenoxolone (CBX), Probenecid (PBN), and Spironolactone, along with chemically synthetic compounds 10Panx. Both genetic modulation of Panx expression and pharmacological manipulation have demonstrated the channels’ critical involvement in various human pathologies, establishing them as promising therapeutic targets for clinical intervention. In this review, we will specifically examine the signaling regulatory functions of Panx channels in the processes of inflammation and tumorigenesis; systematically evaluate the therapeutic potential of Panx inhibitors in these pathological contexts, critically analyze current research limitations, and strategically propose future perspectives in Panx channels and its inhibitors research.